Happiness as an impossible horizon: on Andrei Platonov and Michel Houellebecq (Colloquia Comparativa Litterarum, 2025)
This article offers an analysis of the short story Dzhan by Andrei Platonov written in the early 20th century, and the novel The Possibility of an Island by Michel Houellebecq penned in the early 21st century. Genre-wise, both works navigate between utopia and dystopia. The text explores the potential for happiness in conditions of a primordial, pre-modern society (in Dzhan) and in the context of hypermodernity (The Possibility of an Island). The article questions: What happens to the perfect utopian machine and the pursuit of happiness today? Or, how does the absence of desire and imagination, the lack of a lasting yearning for future horizons, as an essential existential aspect of humanity, undermine even the inhuman itself?
Keywords: Andrei Platonov; Michel Houellebecq; Dzhan (Soul); The Possibility of an Island; utopia; dystopia; happiness; eternal life